2017
DOI: 10.1007/s13679-017-0277-4
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Evidence for Paediatric/Adolescent Bariatric Surgery?

Abstract: Purpose of ReviewIn spite of the increasing prevalence of severe and complex obesity in children, surgery as a potential management option is still not widely accepted. The purpose of this review is to examine the evidence for surgical options in the severely obese paediatric population. Increasing evidence supports early rather than later use of bariatric surgery in the treatment of extreme obesity.Recent FindingsPrior to 2007, the feasibility and safety of surgery have been reported by predominantly small, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 59 publications
1
21
0
Order By: Relevance
“…8 Bariatric surgery is considered safe and effective by many to obtain substantial weight loss and resolution of associated comorbidities. 9,10 Despite the favorable results of bariatric surgery in the literature, implementation of this treatment shows a large variety worldwide. While numbers of severely obese adolescents undergoing bariatric surgery in the United States are increasing, surgeons in Europe seem more reluctant to perform such procedures.…”
Section: Introductionmentioning
confidence: 99%
“…8 Bariatric surgery is considered safe and effective by many to obtain substantial weight loss and resolution of associated comorbidities. 9,10 Despite the favorable results of bariatric surgery in the literature, implementation of this treatment shows a large variety worldwide. While numbers of severely obese adolescents undergoing bariatric surgery in the United States are increasing, surgeons in Europe seem more reluctant to perform such procedures.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence in this population group is limited, and more epidemiological studies are needed to highlight the main benefits and their impact in the short and long term . A Cochrane systematic review of 2015 regarding the role of bariatric surgery in adolescents indicated that this intervention, independently of surgical techniques, had beneficial results in some comorbidities of obesity such as dyslipidemia and type 2 DM and a positive impact on the quality of life of the paediatric patient . The use of vitamin supplements is recommended because in the absence of these, inadequate absorption of calcium, vitamins A, C, and D, iron, and vitamins B1, B6, B9, and B12 can occur, which can lead to nutritional deficiencies and clinical symptoms of peripheral neuropathy (B12 deficiency), beriberi syndrome (B1 deficiency), iron deficiency anaemia, osteopenia, or osteoporosis .…”
Section: Surgical Managementmentioning
confidence: 99%
“…The use of vitamin supplements is recommended because in the absence of these, inadequate absorption of calcium, vitamins A, C, and D, iron, and vitamins B1, B6, B9, and B12 can occur, which can lead to nutritional deficiencies and clinical symptoms of peripheral neuropathy (B12 deficiency), beriberi syndrome (B1 deficiency), iron deficiency anaemia, osteopenia, or osteoporosis . The monitoring of the paediatric patient at the metabolic and psychosocial level must be guaranteed for at least 2 years after surgery …”
Section: Surgical Managementmentioning
confidence: 99%
“…Severe obesity is defined as a BMI ≥ 99th percentile for age and gender, equivalent to a BMI Z-score of +2.5, which is an adult BMI of 30 kg/m 2 ( 4 ). A high BMI for age, especially in those with severe obesity, is associated with early co-morbidities, such as type 2 diabetes, non-alcoholic fatty liver disease (NAFLD), non-alcoholic steatohepatitis (NASH), dyslipidemia, obstructive sleep apnea (OSA), hypertension (HTN), heart disease, and early mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is the most significant threat to the health of younger generations due to its cumulative health impact ( 4 ). Current indications for WLS in adolescents include a BMI ≥35 kg/m 2 or ≥120% of the 95th percentile with clinically significant comorbid conditions such as OSA (apnea-hypopnea index (AHI) >5 events/h), type 2 diabetes, idiopathic intracranial hypertension, NASH, Blount's disease, slipped capital femoral epiphysis, gastroesophageal reflux disease or HTN; or BMI ≥40 kg/m 2 or ≥140% of the 95th percentile ( 6 ).…”
Section: Introductionmentioning
confidence: 99%